Legal rights of refugee and asylum seeking children in Malaysia / Sarirah Che Rose, Rohayati Hussin and Azni Syafena Anden Salamat - Che Rose, Sarirah; Hussin, Rohayati; Salamat, Azni Syafena Anden (Research Management Institute (RMI), 2012)
Malaysia has long served as temporary host for refugees and asylum seekers fleeing persecution and armed conflict. Despite the increasing number of refugees and asylum seekers, Malaysia is still one of the few remaining countries in the world that has not ratified the 1951 Refugee Convention and its Protocol 1967. Consequently, refugees and asylum seekers are not recognized in Malaysia. Notably, Malaysia has ratified the Covention on the Rights of the Child on 17th. of February, 1995. This is important to refugee and asylum seeking children because it sets the most standards concerning children. This research will therefore, examine the legal rights of refugee children in Malaysian as set forth in the international conventions. Through this study recommendations will be made to uphold the refugee and asylum seeking children's rights in Malaysia as set forth in the international conventions to which Malaysia is a signatory. The methodology chosen for this research is qualitative in which the findings are based upon both primary and secondary data. This study may form the basis for policy maker's consideration in formulating a legislation that specifically addresses the matter of refugee and asylum seeking children in Malaysia. It also provides food for thought for NGOs, legal practitioners, academics, students and those who concern with the rights of refugee and asylum seeking children in Malaysia.